Advances in treatment of chronic thromboembolic pulmonary hypertension. Issue 212 (April 2022) - Tzoumas, Andreas; Peppas, Spyridon; Sagris, Marios; Papanastasiou, Christos A.; Barakakis, Paraschos Archontakis; Bakoyiannis, Christos; Taleb, Adam; Kokkinidis, Damianos G.; Giannakoulas, George
Abstract: Chronic Thromboembolic Pulmonary Hypertension (CTEPH) is a progressive pulmonary vascular disease which can lead to right heart failure and death, if left untreated. CTEPH is caused by persistent obstruction of large, middle-sized, or distal pulmonary arteries due to limited thromboembolic resolution in the pulmonary vascular arterial tree. Every patient with CTEPH should undergo evaluation for Pulmonary Endarterectomy (PEA) after referral to institutions with an experienced multidisciplinary CTEPH team. Although management of distal thromboembolic lesions with PEA remains a challenge due to their difficult accessibility, limited distal CTEPH is not considered an absolute contraindication for PEA, as more expertise surgical teams operate on them successfully. Furthermore, in up to 30–50% of patients who undergo PEA, curative treatment is not achieved due to incomplete thrombi removal or extensive pulmonary microvascular disease. Medical therapies that target the underlying pulmonary microvascular disease can offer symptomatic and hemodynamic benefits, although they do not deal with the core mechanism of the disease which is the removal of thromboembolic material from pulmonary vasculature. Recent research has provided evidence suggesting balloon pulmonary angioplasty (BPA) is a reasonable treatment option for inoperable CTEPH and recurrent/persistent pulmonary hypertension after PEA. Advancements in diagnostic modalities and refinements of BPA technique have decreased the complication rate and increased its beneficial effects in hemodynamics, symptoms, right ventricular function and long-term survival. Ongoing trials and future prospective cohorts will provide evidence regarding the optimal selection of patients and lesions prone to BPA treatment along with hybrid therapeutic strategies combining pharmacological therapy, PEA and BPA, which can potentially change the standard of care in CTEPH. Highlights: PEA is the gold standard treatment against CTEPH and should be pursued in every operable CTEPH patient BPA serves as a complementary treatment modality to PEA procedure and should be pursued in inoperable CTEPH patients Long-term anticoagulation with VKA is the first-line treatment for CTEPH patients regardless of the intervention (PEA, BPA) NOACs use increases over the years and further studies are needed to evaluate their safety and efficacy